A influência dos fatores contingenciais nas práticas de contabilidade gerencial baseadas nos PGCG em cooperativas agropecuárias brasileiras - Silva, Marcilene Pereira da (2022)
Management accounting has sought to meet the needs of managers, improving their practices, in this sense the CGMA prepared a project in which the PGCG were appointed, whose objective is to guide management accounting practices helping to improve the decision making process, however It is important to highlight that management accounting practices can be influenced by several factors, which are beyond the domain of organizations and their managers, this premise is addressed by the theory of contingency. Therefore, the objective of this study was to analyze the influence of contingency factors “environment, strategy, technology and organizational culture” on management accounting practices based on PGCG in Brazilian agricultural cooperatives. It is a quantitative study, of the survey type, which made use of a structured questionnaire for data collection. The study was developed from 67 Brazilian agricultural cooperatives linked to the OCB system. The variables addressed in this work were contingency factors: environment, strategy, technology and organizational culture and management accounting practices based on the PGCG. Regarding data analysis procedures, descriptive statistics and Spearman correlation analysis were used. The results of this research show a strong correlation between the contingency factors discussed in the study and the management accounting practices based on the PGCG, in which most of the variables showed a positive correlation, when one variable increases the other tends to increase in a similar proportion and for other variables this correlation was negative, demonstrating that the variables act in opposite directions.